2017
DOI: 10.1155/2017/7313090
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Variable Stress Is Responsible for Lipid and DNA Oxidative Disorders and Activation of Oxidative Stress Response Genes in the Brain of Rats

Abstract: Chronic environmental stress is associated with reactive oxygen species (ROS) overproduction and the pathogenesis of depression. The purpose of this study was to evaluate biochemical and molecular changes associated with ROS generation in the brains of rats submitted to chronic variable stress. Male Wistar rats (50–55 days old, weighing 200–250 g) were divided in two groups (n = 10): control and stressed. Rats in the stressed group were exposed to stress conditions for 40 days. The animals were decapitated and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 66 publications
2
45
0
Order By: Relevance
“…Thus, the expression of glucose transporters can be raised in the brain as a response to an enhanced demand for glucose resulting in the support of energy metabolism. The research has shown that stress events have a significant impact on ROS generation in brain and it can cause an increase in energy demand (2,34). Repeated and unpredictable stress situations increase ROS generation, which can damage a variety of cell macromolecules, including those that constitute the electron transport system, therefore disrupting mitochondrial function (2,34,35).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, the expression of glucose transporters can be raised in the brain as a response to an enhanced demand for glucose resulting in the support of energy metabolism. The research has shown that stress events have a significant impact on ROS generation in brain and it can cause an increase in energy demand (2,34). Repeated and unpredictable stress situations increase ROS generation, which can damage a variety of cell macromolecules, including those that constitute the electron transport system, therefore disrupting mitochondrial function (2,34,35).…”
Section: Discussionmentioning
confidence: 99%
“…The research has shown that stress events have a significant impact on ROS generation in brain and it can cause an increase in energy demand (2,34). Repeated and unpredictable stress situations increase ROS generation, which can damage a variety of cell macromolecules, including those that constitute the electron transport system, therefore disrupting mitochondrial function (2,34,35). It is possible that in chronic stress, we can observe a disturbance in energy production due to mitochondrial damage by excess ROS, which may activate signaling pathways involved in cellular adaptation to various types of stress.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations